2020
DOI: 10.1155/2020/3179193
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Pregnancy and Associated Factors among Pregnant Women Attending Antenatal Care at Bako Tibe District Public Health Facility, Oromia Region, Ethiopia

Abstract: Background. A pregnancy is described unintended if it is either unwanted or mistimed. The former occurs when no child or no more children are desired, and the latter is when the conception occurs earlier than the desired time, but wanted later. Unwanted pregnancy causes a serious health, economic, and social problem to the woman and her family. In the study area, there is limited data on unintended pregnancy. Therefore, this study fills this gap by studying the magnitude of unintended pregnancy and its associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 12 publications
5
30
0
Order By: Relevance
“…The present study found that nearly one third of women with UP were multigravida. This finding was almost similar to Goshu [26] who found that when gravidity increased, the probability of exposure to UP was increased. Moreover, Fite [18] revealed that women whose gravidity 5 and above were 3.88 times more likely to have unintended pregnancy than those whose gravidity 1-2.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study found that nearly one third of women with UP were multigravida. This finding was almost similar to Goshu [26] who found that when gravidity increased, the probability of exposure to UP was increased. Moreover, Fite [18] revealed that women whose gravidity 5 and above were 3.88 times more likely to have unintended pregnancy than those whose gravidity 1-2.…”
Section: Discussionsupporting
confidence: 88%
“…This association may be due to illiteracy, poverty, higher fertility rate, limited availability of health services, and poor utilization of social and health services that characterize rural areas. This finding was matched with Goshu [26] who found that the majority of the studied women were lived in rural areas and unemployed. On the other hand, Mohamed [19] showed that employed women were more likely had UP than unemployed women.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas mistimed pregnancy is described as when the pregnancy occurs earlier to the desired time but needed later. 4 In general, unintended pregnancy is a pregnancy that occurred without consideration of whether or not contraception was being used but the pregnancy was not wanted at the time conception occurred. 5 , 6 It is a public health issue globally, and it is one of the major reproductive and sexual health problem which ends with a higher risk of mortality and morbidity among reproductive age groups of women.…”
Section: Introductionmentioning
confidence: 99%
“…Age as a determinant unintended pregnancy was also found in previous studies 9,14,15 . Age other than related to the unpreparedness of women when they were teenagers 16,17 , also related to the number of children desired and the reproductive ability of women 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis found that husband/partner only decision making was a risk factor for unintended pregnancy among childbearing age women in Indonesia. This condition is related to the lack or deadlock of communication between women and their partners 14,18,19 . Several previous studies have found the same information, unintended pregnancy is closely related to women's independence in making decisions about their reproductive health 25,26 .…”
Section: Discussionmentioning
confidence: 99%